Advances in High-Entropy Alloys Materials Research, Exotic Properties and Applications - Kitagawa, Jiro (IntechOpen, 2021)
High-entropy alloys (HEAs) are a new class of materials attracting attention from researchers all over the world. This book provides a comprehensive overview of the research on HEAs, as well as discusses the mechanical, physical, and chemical properties of new HEAs and their potential applications. Chapters cover such topics as HEA superconductors, HEA composites, high-entropy superalloys, artificial intelligence in HEA design, and more.